Research on Cavitation Characteristics of Series Venturi - HAN Gui-hua; YANG Xu-dong; CHEN De-yu; LI Da-wei; ZHAO Meng-shi; PEI Yu; YAO Hong-bin; YAO Li-ming (Journal of Harbin University of Science and Technology)
In order to study the cavitation characteristics of series venturi, a cavitation model of venturi is established in this paper. Based on the change of inlet pressure and water temperature, the evolution process of cavitation effect in single-stage and multi-stage series venturi is studied. Taking the average gas holdup as the characterization of cavitation effect, the relationship between the series number of Venturi tubes and cavitation characteristics is obtained, the matching relationship between the exit cone angle and Venturi tube is obtained, and the evolution law of cavitation effect between single-stage and multi-stage series is obtained. In order to verify the cavitation characteristics of series Venturi tubes, the conductivity of cavitation medium (water) is used as the experimental characterization.The experimental results show that: under the experimental pressure (< 1MPa), the conductivity of singlestage venturi water sample is greater than that of series tube, and the conductivity of water sample increases with the increase of cavitation time; the conductivity can be used as one of the parameters to characterize the cavitation effect. This paper provides guidance for the relationship between cavitation and pressure and temperature, and provides a new method for the experimental characterization of cavitation effect.